Um estudo sobre o trabalho de duas professoras de maternal na escola municipal de ensino integral Ciria de Nazaré Tulosa dos Santos no município de Belém - PA - SEABRA, Vivian Araújo Ferreira (2022)
The present work analyzes the work of two kindergarten teachers through questionnaires answered by them, on the perspectives of observation, planning and care and education. In which it raises questions about their pedagogical work, from an ethical and responsible perspective. Analyzing whether care and education are carried out in their practice, aiming at the development of the student. Starting from the idea that the teacher is a crucial agent in the child's learning and that he/she needs to ethically care for his/her student with an affective perspective, seeing his/her student as a child who needs to have his/her rights assured. Because when care gains an ethical dimension, it enters the sphere of education and they become one. Thus, the work will show the difficulties in preparing the research, as well as the results from the perspective of the teachers, in which they understand how much observation may be necessary for the student's knowledge and which directly favors the planning of care and education activities.